THE RELATIONSHIP OF THE LEVEL OF EMOTIONAL MATURITY WITH THE LEVEL OF STUDENTS' AGGRESSION - Yuarini Wahyu Pertiwi; Anissa Syifa Azzahra; Brahua; Hanni, Hanni Pratiwi; Novela; Zaidi Naufal Al Fayyaadh (Journal of Psychology and Social Sciences, 2023)
This study aims to determine whether there is a relationship between the level of emotional maturity and the level of aggression at the Faculty of Psychology UIN Raden Fatah Palembang. Where the subjects we are looking for ourselves from the 2021 class of psychology faculty students at UIN Raden Fatah Palembang, Aggression Behavior itself is an act which aims to hurt someone either psychologically or physically. This aggression behavior is carried out by people who do not have emotional maturity where they often experience certain emotions such as angry emotions. The research method we conducted was a quantitative method using a cross sectional design. The sample we took amounted to 33 respondents from the Faculty of Psychology UIN Raden Fatah Palembang. The correlation coefficient (r) is 0.115 with a significance of 0.524. Variable X to variable Y has a correlation with the degree of relationship, namely moderate correlation and the form of the relationship is positive because p < 0.05 (0.000 < 0.05). So it can be concluded that emotional maturity and aggression have a strong correlation. This research is reinforced by research conducted that there is a negative and significant relationship between emotional maturity and aggression behavior of residents of the Ayu Sempaja Samarinda Dormitory Complex, meaning that the lower the emotional maturity of dormitory residents, the higher the aggressive behavior they have. Thus it can also be concluded that the hypothesis (H1) proposed in this study can be accepted.